COGNITIVE BEHAVIORAL THERAPY FOR CAREGIVERS: SLAYING GRIEF AND LOWKEY BOOSTING SOCIAL SUPPORT - Neevatha Palani; Kannan Jayaraman; Shankar Shanmugam Rajendran; Marudhan Anbalagan; Balasubramaniyan Srividhya; Velan Dhayanithipalani; Shanmugapriya Shanmugasundharam (The Bioscan, 2025)
Caregivers of terminally ill patients often face high levels of grief, anxiety, and emotional exhaustion, with studies showing up to 50% affected by severe grief. Lack of social support worsens their mental health and increases feelings of isolation. Cognitive behavioural therapy (CBT) is beneficial by improving coping mechanisms and altering harmful thought patterns. Materials and Methods: This quasi-experimental study involved 60 caregivers participants from Rajiv Gandhi Governement General Hospital, Chennai. Participants were divided into an experimental group, which received cognitive behavioral therapy as interventions, and a control group, which received routine care. Assessments of grief and social support were conducted at baseline and post-intervention using standardized scales. Data were analysed using SPSS v26, with descriptive and inferential statistics at a 5% significance level. Result: The experimental group showed a major decrease in grief scores, especially in behavioral (from 28.57 to 18.30) and emotional reactions (from 20.57 to 9.10), with a total score reduction of 21.73 points (p = 0.001) and total social support score rising from 33.67 to 52.60 (p = 0.001).The control group showed minimal changes in grief score and social support score. Conclusion: The study highlights the critical role of nurses in implementing CBTs to be effective in reducing grief and emotional distress and enhance social support among caregivers of terminally ill. Overall, it promotes emotional resilience and improves the caregiving experience.